2019
DOI: 10.1186/s12978-019-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care presentation and engagement in the context of sex work: exploring barriers to care for sex worker mothers in South Africa

Abstract: Background Late presentation combined with limited engagement in antenatal care (ANC) increases risk of vertical transmission among mothers living with HIV. Female sex workers (FSW) have more than four times greater burden of HIV than other women of reproductive age in South Africa and the majority of FSW are mothers. For mothers who sell sex and are at increased HIV acquisition risk, timely and routine ANC seeking is especially vital for prevention of vertical transmission. This study represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Reliance on condom-only as a contraceptive method by the FSWs in this study has also been reported by FSWs from other parts of the country (16). However, the condom failures were the predominant events in FSWs' lives in this study and other studies as well (15,24,43). The consequent unintended pregnancies were frequent among the FSWs in this study, as reported by other researchers (6,20,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 85%
“…Reliance on condom-only as a contraceptive method by the FSWs in this study has also been reported by FSWs from other parts of the country (16). However, the condom failures were the predominant events in FSWs' lives in this study and other studies as well (15,24,43). The consequent unintended pregnancies were frequent among the FSWs in this study, as reported by other researchers (6,20,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 85%
“…Delayed seeking of antenatal care was found in a South African study [ 27 ]. This was attributed to late pregnancy detection, alcohol and substance use, and discontent with previous healthcare-related experiences.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Such barriers also decrease access to sexual and reproductive health care services, including contraception, which may result in unplanned pregnancies and excess morbidity and mortality from complications of unsafe abortion. 11,12 In contrast to the many studies on FSW morbidity, we only identified four English-language studies on FSW mortality published since 2000. Each of these studies used a different methodology to record deaths of FSW.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 Such barriers also decrease access to sexual and reproductive health care services, including contraception, which may result in unplanned pregnancies and excess morbidity and mortality from complications of unsafe abortion. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%